A CROSS-SECTIONAL STUDY OF THYROID DISORDER IN PATIENTS WITH TYPE 2 DIABETES MELLITUS IN A TERTIARY CARE HOSPITAL - SHEKHAR, RAVI (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The objectives of the study were to assess thyroid function in diabetes mellitus by estimating free T3, free T4, and TSH in type 2 diabetic subjects, and the correlation between TSH and HbA1c. Methods: It was a cross-sectional study. The study was conducted at the Sapthagiri Institute of Medical Science in Bengaluru, Karnataka, and a total of 75 newly diagnosed type 2 diabetes mellitus patients were enrolled for this study from January 2020 to January 2021. Results: The prevalence of thyroid disorder among type 2 diabetes mellitus patients was 14.7% (11). Out of 11 cases, 4 (5.4%) cases belonged to hypothyroidism, 1 (1.3%) case was hyperthyroidism, 6 (8.0%) cases were subclinical hypothyroidism, and subclinical hyperthyroidism cases were not found in this study. Normal thyroid function was found in 64 (85.3%) cases. Conclusion: Thyroid disorders are more prevalent in people with type 2 diabetes. Female diabetics are more likely to have this finding. Subclinical hypothyroidism is the most frequent thyroid disorder. Thyroid disorders are more commonly associated with diabetes among people with diabetes who have poor metabolic control.